CERTYFIKATOWE TESTY Z JĘZYKA POLSKIEGO I ANGIELSKIEGO NA POZIOMIE C2 W UJĘCIU PORÓWNAWCZYM - Banach, Małgorzata (Neofilolog, 2019)
The amendment to the Polish Language Act in 2015 has resulted in significant changes in the system of the state certificate examinations in Polish as a foreign language. One of the changes is a revised format of the certificate examination at C2 level. The author begins by briefly presenting the recent revisions to the test. The Polish examination is then compared with its English equivalent: C2 Proficiency, a renowned British test which has undergone numerous changes since its first administration in 1913. The comparative analysis is focused on the structure of both examinations and their parts, task types that are used and skills that are tested. Through showing similarities and differences between the analyzed language proficiency tests the author reflects on practical implications of various choices made by experts who are responsible for test design and development.